(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Industrial effluents, heavy metals, and agricultural runoff have mutagenic, carcinogenic, immunomodulatory, and teratogenic effects on soil physiochemical features, posing a major health and environmental risk. As a result, soil contamination necessitates the use of a variety of physiochemical approaches and procedures to reduce the severity of the damage. Among these, bioremediation has been proved to be a feasible option for restoring contaminated regions at a reasonable cost. Owing to the difficulties in identifying the best biomonitoring technology for each type of pollution as well as the paucity of studies on soil phytoremediation aided through the use of specific compounds, we assessed the key in situ or ex situ procedures, their current quality, and applicability. The first portion delves into the specific properties of each kind of pollution, while the second half introduces contemporary bioremediation methods and their primary applications, accompanied by a comprehensive study of their benefits and drawbacks.